SURVEY COMMUNITY SATIFACTION INDEX DALAM PELAKSANAAN PROGRAM CSR PT ANTAM Tbk - Maemanah; Anggoro Dwi Saputro; Firja (Journal Publicuho, 2022)
PT ANTAM Tbk as one of the mineral mining companies in Indonesia that is committed to implementing GCG has carried out its business operations that are oriented towards sustainable development. The existence of a CSR program is an important thing that is always optimized and improved in quality. Therefore, in the implementation of the CSR program, PT ANTAM Tbk continues to make efforts to minimize program failures by evaluating the implementation of the CSR program. In this study, the concept used is the result of an analysis of several sources, namely from the Ministry of Environment and Forestry (KLHK in the KLHK Proper Green Guidebook (2013) explains that the CSI assessment consists of several aspects that are measured, including business indicators, effectiveness, efficiency, and quality.The effectiveness of community development programs is also taken from Sari (2019) sources to complete the indicators needed according to the conditions in the field. In the results, the CSI value of PT ANTAM UBPN Sultra is very good, with a value of 89.56, this value is obtained because the average program recipient is satisfied with the program carried out by PT ANTAM UBPN Sultra's CSR. The programs are implemented in accordance with the needs of the community and the performance of the program is also good. Although the value of community satisfaction is high, the program still needs to make improvements.